Clinique du travail et santé au travail : ouvertures, perspectives et limites - Jean-Yves Bonnefond; Yves Clot (Perspectives Interdisciplinaires sur le Travail et la Santé)
Based on an experiment in the automotive industry, this article contributes to further reflection, in the work clinic field, on how to study work health questions. These questions are at the center of social debates about the relationship between work quality and quality of life. After specifying the reason for the intervention, that is to « restore » the workers’ capacity to act, we try to show how the workers and their hierarchies can act together to reconfigure work organization so as to achieve well-done, high-quality work. Based on the example presented in the text, we argue for a practice of work psychology whose goal is to introduce more professionalism into the workplace. We propose that new activities and functions be experimented so as to test conflictual cooperation between administrators, managers, operators, and trade unions around the theme of work quality. The purpose here is to link workers’ health and their activity performance with the quality of the products manufactured and services delivered.